Study protocol for the G-SPIRIT trial: a randomised, placebo-controlled, double-blinded phase III trial of granulocyte colony-stimulating factor-mediated neuroprotection for acute spinal cord injury. Issue 5 (5th May 2018) - Koda, Masao; Hanaoka, Hideki; Sato, Takatoshi; Fujii, Yasuhisa; Hanawa, Michiko; Takahashi, Sho; Furuya, Takeo; Ijima, Yasushi; Saito, Junya; Kitamura, Mitsuhiro; Ohtori, Seiji; Matsumoto, Yukei; et al.
Abstract : Introduction: Granulocyte colony-stimulating factor (G-CSF) is generally used for neutropaenia. Previous experimental studies revealed that G-CSF promoted neurological recovery after spinal cord injury (SCI). Next, we moved to early phase of clinical trials. In a phase I/IIa trial, no adverse events were observed. Next, we conducted a non-randomised, non-blinded, comparative trial, which suggested the efficacy of G-CSF for promoting neurological recovery. Based on those results, we are now performing a phase III trial. Methods and analysis: The objective of this study is to evaluate the efficacy of G-CSF for acute SCI. The study design is a prospective, multicentre, randomised, double-blinded, placebo-controlled comparative study. The current trial includes cervical SCI (severity of American Spinal Injury Association (ASIA) Impairment Scale B/C) within 48 hours after injury. Patients are randomly assigned to G-CSF and placebo groups. The G-CSF group is administered 400 µg/m 2 /day×5 days of G-CSF in normal saline via intravenous infusion for 5 consecutive days. The placebo group is similarly administered a placebo. Our primary endpoint is changes in ASIA motor scores from baseline to 3 months. Each group includes 44 patients (88 total patients). Ethics and dissemination: The study will be conducted according to the principles of the World Medical Association Declaration of Helsinki and in accordance with the Japanese Medical Research Involving Human Subjects Act and other guidelines, regulations and Acts. Results of the clinical study will be submitted to the head of the respective clinical study site as a report after conclusion of the clinical study by the sponsor-investigator. Even if the results are not favourable despite conducting the clinical study properly, the data will be published as a paper. Trial registration number: UMIN000018752.